A151 RISK FACTORS FOR VENOUS THROMBOEMBOLISM AFTER HOSPITAL DISCHARGE IN PATIENTS WITH INFLAMMATORY BOWEL DISEASE: A SYSTEMATIC REVIEW AND META-ANALYSIS. (21st February 2022) - Gozdzik, M; Unninayar, D; Sarker, A; Chin Koon Siw, K; McCurdy, J
Abstract: Background: Inflammatory bowel disease (IBD) is a chronic inflammatory condition which is independently associated with venous thromboembolism (VTE). Although the absolute risk of VTE is greatest during hospitalization, the risk remains elevated in the early post-discharge period. The risk factors for VTE during this vulnerable period remain unknown. Aims: We performed a systematic review and meta-analysis to determine risk factors for VTE in the post discharge period among adult patients with IBD. Methods: We performed a systematic search of Embase, MEDLINE, and the Cochrane Central Register of Controlled Trials from inception through April 29, 2021 for publications that reported risk factors for VTE during the post-discharge period among patients with IBD. Study eligibility was assessed independently in duplicate without age or language restriction. We defined the post-discharge period as within 6 months of discharge. Pooled summary estimates of adjusted hazard/odds ratios, when available, were calculated for individual risk factors using random effects model with 95% confidence intervals. The analysis was performed when a minimum of three studies were available for a given risk factor. Heterogeneity was assessed using I 2 statistic. Study quality was assessed using an adapted version of the National Institute of Health criteria. Results: We identified 10 studies from a total of 4339 abstracts that met our inclusion criteria: 8 population-based studies, 1 multicenter observational study and 1 single center observational study. Risk factors for post-discharge VTE were assessed at 6 weeks in 1 study, 1 month in 5 studies, 3 months in 2 studies, and 6 months in 2 studies. The variables assessed in our meta-analysis are reported in Table 1. Exposure to corticosteroid (odds ratio [OR], 1.77; 95% CI, 1.53–2.06) but not biologics (OR, 1.21; 95% CI 0.80–1.82) was associated with an increased risk of VTE. Furthermore, greater length of stay (OR 1.49; 95% CI, 1.01–2.20), ulcerative colitis (OR 1.41; 95% CI, 1.19–1.66), history of malignancy (OR 1.35; 95% CI, 1.12–1.62), and surgery during admission (OR 1.26; 95% CI, 1.12–1.42) but not female sex (OR 0.98; 95% CI, 0.88–1.10) or surgery type (OR 1.09; 95% CI, 0.75–1.57) were associated with increased risk of VTE after discharge. Overall, the study quality was rated as fair. Conclusions: In our meta-analysis, which consisted of moderate quality of evidence, we identified multiple risk factors associated with VTE in the post-discharge period. This work will help inform which factors should be considered for developing point of care clinical predictive models to help guide when extended VTE prophylaxis is required. Funding Agencies: None